The Relationship between language learning strategies and teacher’s mediating role - Sorayya Behroozizad; Radha M.K Nambiar; Zaini Amir (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
Research on second and foreign language learning strategies has mushroomed over the last three decades and some very valuable studies have been conducted. Most, however examine strategies from a cognitive perspective, with fewer studies examining the emergence of learning strategies from a sociocultural perspective. In particular, the role of sociocultural mediation has not been specifically investigated as a solution for (English as a Foreign Language) EFL learners’ difficulties by Iranian researchers. This study investigates the role of mediation in Iranian EFL learners’ strategy development and use by reconfiguring the culture of the EFL listening-speaking classroom through teacher’s scaffolding techniques. Framed by sociocultural theory and activity theory the study collects data using the learner-diary, observation field notes and student and teacher interviews. The findings indicated that the participants’ activities are mediated to a considerable extent by the opportunities provided through the teacher’s scaffolding. The findings suggest that teachers should utilize different forms of mediation in their teaching to help learners harness the advantage of the efficacy of communicative classrooms.